ESRA19-0389 Pulse dosing of 10 khz paresthesia-independent spinal cord stimulation provides same efficacy with substantial reduction of device recharge time. (30th August 2019) - Provenzano, D; Yu, C; Verrills, P; Guirguis, M; Harrison, N; Bradley, K
Abstract : Background and aims: High frequency 10 kHz paresthesia-independent spinal cord stimulation (10kHzSCS) has demonstrated statistical and clinical superiority over traditional, low-frequency paresthesia-based SCS in relief of chronic back and leg pain. The purpose of this study is to assess the ability of percent pulse dosing (%PD=alternating 10kHzSCS ON and OFF times) to reduce device recharge time while maintaining efficacy. Methods: Permanently-implanted subjects successfully using 10kHzSCS at 100%PD to treat back pain with or without leg pain for >3 months were enrolled. After a 1-week baseline period of documenting their pain using a 0–10 numerical rating scale (NRS) using 100%PD, all subjects were reprogrammed to 14%PD for 7–10 days. If subjects preferred 14%PD to 100%PD, they were programmed to 3%PD; otherwise, they were programmed to 50%PD; subjects used this program for 7–10 days. After these initial%PD evaluations, each subject entered a 3-month uncontrolled observational period where the subject was requested but not limited to use their most preferred%PD program. At the end of 3 months, the subject completed a 7-day NRS diary and indicated a final%PD program preference. Results: 6/15 subjects preferred 3%PD, 3/15 preferred 14%PD, 3/15 preferred 50%PD, and 3/15 preferred 100%PD. Average daily charge durations: 3%PD=8.6±0.5 min, 14%PD=14±7 min, 50%PD=33±3.3 min, 100%PD=38.6±6.5 min. Average back pain scores: 3%PD=1.8±1.4, 14%PD=2.0±1.7, 50%PD=4.1±0.7, 100%PD=1.7±1.4, all P>0.1 from 100%PD. Conclusions: In this study, 80% of 10kHzSCS responders maintained efficacy and reduced device charging times approximately 64% using <100%PD. These trends suggest that 10kHzSCS therapy may be successfully employed with device charging times approximately 30% shorter than traditional SCS.